Antimicrobial and antioxidant therapy with bioactive plant molecules on Fe3O4 phytohybrid nanoplatforms - Janesline Fernandes; Teotone Vaz; Tushar S. Anvekar (SpringerOpen, 2021)
Abstract Background Nanobiomedicines have gained increasing attention for their potential to improve efficacy and are emerging as a promising therapeutic paradigm. Magnetic nanoconjugates loaded with bioactive drugs have the advantage of sustained circulation in the bloodstream and significantly reduced toxicity of therapeutic agents in a precise manner. The well-developed surface chemistry of Fe3O4 has led to the development better tools, promoting them as nanoplatforms with potential technological applications in biomedical sciences. Results Fe3O4 phytohybrids with Laxmitaru extract as the primary coating and loaded with Eugenol and Ylang-Ylang essential oils were successfully synthesized. The X-ray diffraction technique has revealed the high purity nanoparticle materials, as no additional impurity peaks were observed. Fourier transform infra-red spectra have confirmed the presence of a primary coating of Laxmitaru extract and a secondary layer of essential oil, as additional peaks and broadening are observed in drug-loaded Fe3O4 nanoparticles. Magnetic susceptibility values indicate the material's superparamagnetic nature. Transmission electron microscopy images have ensured that the particles were spherical, monodispersed, and in the range of 4.30 nm to 13.98 nm. Antimicrobial studies show inhibition zones on the microorganisms S. Aureus and E. Coli with enhanced activity. Drug entrapment efficiency studies revealed the encapsulation of drug molecules onto Fe3O4-Laxmitaru composite. Dynamic light scattering studies confirm the increase in hydrodynamic size, indicating the loading of essential oils and the decrease in polydispersity index ensures monodispersed nanoparticles. The antioxidant study showed the essential oils retained their antioxidant activity even after they were conjugated on Fe3O4-Lax composites. Conclusions Laxmitaru phytochemical-coated Fe3O4 nanoparticles were successfully conjugated with Eugenol and Ylang-Ylang essential oils. Our results provide a model therapeutic approach for the development of new alternative strategies for enhancing antimicrobial and antioxidant therapy, with potential advantages in the field of nanobiomedicine.